Evaluasi Pelaksanaan Kurikulum Merdeka di SMK Negeri 1 Pariaman - Ramadhani, Atsil Nabila; Haq, Syaiful; Silalahi, Juniman; Jufri, Windry Novalia (Lembaga Yasin AlSys, 2025)
The Merdeka Curriculum is designed to improve the quality of education through a student-centered learning approach; however, in its implementation at SMK Negeri 1 Pariaman, several challenges were found that hindered the achievement of these objectives. This study aims to evaluate the implementation of the Merdeka Curriculum at SMK Negeri 1 Pariaman using the CIPP evaluation model (Context, Input, Process, and Product). The method used is descriptive research with a mixed method approach, involving 52 respondents consisting of the school principal, the vice principal for curriculum, DPIB teachers, and XI DPIB students. Data collection techniques were carried out through questionnaires, interviews, observations, and documentation. The results indicate that in the category of